New directions for the realisation of SDGs given the economic and welfare costs incurred by air pollution - Jasińska-Biliczak, Anna; Ikwuwunna, Eugene (Frontiers in Environmental Science, 2023)
Air pollution is a multidisciplinary research field, which affects sustainable development and sustainable development goals (SDGs). Its multi-level cause and effect shows the direct influence of air pollution on human health, standards and costs of living, health treatment, and economies of states. Poor air quality, as a SDGs factor, may affect both: lower well-being and economic growth. As developed economies have faced problems due to poor air quality, they have worked out solutions based on their technological engagement. However, emerging economies are still facing poor air quality as a main problem for their economic growth. The particulate matter factor, according to the Air Quality Study, was used as the basis for comparative and statistical research. The study’s findings indicate that air pollution causes serious impacts relating to workforce productivity, absence from work, mortality, and even lower crop yields. There is an obvious research gap in the investigated field of comparing studies according to air pollution as SD, understood as an economic concept, factor. The current study fulfils this gap, contributes to the knowledge base about the factors affecting human development, and expands the statistical data based on findings from a comparison between Poland and Germany on their performance on air quality. The approach is novel for pointing to air pollution as the proposed focus of research for the realisation of SDGs.